Comparing internal and external impacts of sustainable innovation: An exploratory study - Wasseem Abaza (Journal of Global Entrepreneurship Research, 2017)
Sustainable business impact is growing within the field of impact assessment, however, the field, specifically in regard to Entrepreneurship, would benefit from theory based on comparisons of external and internal impacts of environmental and social innovation. This exploratory study bridges this gap by analyzing an aggregate of case studies of sustainable innovation. Significant differences were found in comparing forms of innovations where product focused innovations favored the environment and service or new business usage innovations favored society. Significant differences were also found in comparing external impacts where either a reduction of waste or an increase in clean energy favored environmental innovations while benefits for under-served populations or improvements in markets favored social innovations as expected. The comparison with the internal impacts showed an increase in revenue and sales favored both types of innovations yet a significant difference was still found between the two. Suggested theories for future research are provided.
Keywords: 650; Sustainability; Impact assessment; Corporate social responsibility